New group decision-making ARCAS approach based on the integration of the SWARA and the ARAS methods adapted for negotiations - Stanujkic, Dragisa; Zavadskas, Edmundas Kazimieras; Karabasevic, Darjan; Turskis, Zenonas; Keršulienė, Violeta (Journal of Business Economics and Management, 2017)
Groups are generally considered to be more effective as compared to single individuals. The practical implementation of Operation Research methods in group negotiations needs simple contexts and clear cause-and-effect relationships easily discernible by everyone. This paper proposes a multi-criteria group decision-making approach allowing decision makers/experts involved in a negotiation process to better express and defend their preferences in the selection of the best alternative. In the proposed approach, the most appropriate alternative is the alternative with the largest number of appearances in the first position or in ranking lists, or the one determined based on negotiations of decision makers/experts. The proposed ARCAS approach is based on the use of the ARAS method, a new normalization procedure, and the SWARA method. In the proposed approach, each decision maker/expert involved in evaluation has an opportunity to set the preferred level of rating for each criterion used in such evaluation. Finally, a case study is presented in order to highlight the proposed approach. The obtained results confirm the usability and efficiency of the proposed approach.